2018
DOI: 10.1021/acs.langmuir.8b00038
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-Dependent Adsorption of CsI at the Muscovite–Electrolyte Interface

Abstract: The interfacial structure of muscovite in contact with aqueous CsI solutions was measured using surface X-ray diffraction for several CsI concentrations (2–1000 mM). At CsI concentrations up to 200 mM, Cs+ adsorption is likely hindered by H3O+, as both cations compete for the adsorption site above the muscovite hexagonal cavity. Above this concentration, more Cs+ adsorbs than is required to compensate the negatively charged muscovite surface, which means that coadsorption of an anion takes place. The I– anion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 29 publications
(85 reference statements)
5
31
0
Order By: Relevance
“…Qualitatively, this observation is consistent with the long residence times of ≈100 ms of Rb + ions on mica that were reported in recent AFM measurements 64 and with the slow ion-exchange rates in X-ray-based Na + –Rb + ion-exchange reactions. 19 According to the AFM studies 65 and recent X-ray measurements, 66 the mica surface is only partially covered by cations for approximately millimolar concentrations. The steepness of the adsorption isotherm in this concentration range in combination with lateral attractions promotes the formation of patches of adsorbed ions.…”
Section: Results and Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Qualitatively, this observation is consistent with the long residence times of ≈100 ms of Rb + ions on mica that were reported in recent AFM measurements 64 and with the slow ion-exchange rates in X-ray-based Na + –Rb + ion-exchange reactions. 19 According to the AFM studies 65 and recent X-ray measurements, 66 the mica surface is only partially covered by cations for approximately millimolar concentrations. The steepness of the adsorption isotherm in this concentration range in combination with lateral attractions promotes the formation of patches of adsorbed ions.…”
Section: Results and Discussionmentioning
confidence: 96%
“…4143 In the absence of added salt, hydronium ions are likely to compensate the intrinsic negative surface charge of mica, as has been suggested by other studies. 17,66 Interestingly, hydronium ions turn out to have a similarly destructive effect on the oscillatory hydration structure of the interfacial water as the bulky Rb + and Cs + ions. The amplitude of the oscillatory force component decreases with decreasing pH, and a slightly attractive monotonic contribution develops (Figure 3).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Majority of studies focused on understanding the properties of ions at solid - aqueous interface have used muscovite mica surfaces in their work. The reasons are that (a) muscovite mica surfaces are easy to cleave, (b) produces atomically smooth surfaces, 22 (c) the framework carries a negative charge compensated by surface potassium ions (K + ), and (d) these surface (K + ) ions can be exchanged with other cations in the presence of aqueous salt solutions 23 26 . Experimental studies using surface force apparatus (SFA) on electrolyte solutions between two mica surfaces have observed short-range repulsive forces due to dehydration of ions beyond a critical concentration of salt solution 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Measurements from the XRR technique provides structural information of interfacial water and ions perpendicular to the surface alone and does not provide in-plane behavior 23 . Recent surface X-ray diffraction (SXRD) studies have found co-ions as well in the Stern layer 23 , 26 . Recent AFM techniques on the mica-RbCl solution (0–4 M) are able to probe in the three dimensional structures of solutions on the surface but still has the limitation to distinguish ion hydration and free water molecules 31 .…”
Section: Introductionmentioning
confidence: 99%